TELEMEDICINE AS AN EFFORT TO IMPROVE PUBLIC KNOWLEDGE TO FIGHT COVID-19 PANDEMIC - Sacharissa Zerlina Tsarwah Thirafi; Triadi Putra Paladan; Bonfilio Neltio Ariobimo; Barizatul Husniyah; Monica Tiara Arum Kinanthi; Gusti Agung Ayu Ira Kencana Dewi; Prima Ardiansah Surya; Yolanda Ayu Yashinta; Zaufy Verlieza Oktaviano Subagyo; Laksmi Wulandari; Linda Dewanti (Journal of Community Medicine and Public Health Research)
The role of the community is an essential part to cut down the COVID-19 chain transmission, a current world pandemic. Knowledge determines a person's healthy behavior that can prevent transmission of COVID-19. This research's goal is to analyze the effect of health promotion via telemedicine on increasing knowledge about COVID-19 prevention in the productive-age population in Indonesia. This study used one group pretest-posttest design and accidental sampling method involving 146 respondents based on the inclusion criteria. The data collection method was carried out by using a questionnaire containing simple and general questions related to COVID-19 that tested subjects before and after telemedicine health promotion. Based on the assessment of the questionnaire through pretest and posttest, there was an increase in the average knowledge after being given health education with telemedicine with p<0.001 (CI 95%). This study shows that telemedicine could significantly increase average knowledge about COVID-19 prevention in the productive-age population in Indonesia.